Buzzer Sebagai Alat Politik Ditinjau Dari Perspektif Penegakan Hukum Di Indonesia - Rizki Kurniawati (Universitas Sang Bumi Ruwa Jurai, 2023)
Buzzers with other meanings of buzzers or their activities called Buzzing have now become the public spotlight, especially when buzzing actions are rampant on various social media platforms. During the election period, Buzzers who use anonymous accounts or organic accounts are often used by pairs of candidate success teams or certain cadres from a political party, Buzzers who are an important part of the election process because they not only function as marketing, but also work to bring down the electability of other candidate pairs including attacking with hate speech in various forms and defending one of the supported candidate pairs. Based on this, this research focuses on the weak implementation of the ITE Law as an extension of the Criminal Code limited only to buzzers and their activities without looking deeper into the